The involvement of non-formal education in students' learning needs during the covid-19 epidemic - Manurung, Paisal; Karimaliana, K; Ansi, Rahma Yunita; Harahap, Dian Anggraini; Ginting, Datulina; Subagiharti, Heni (Universitas Malikussaleh, 2021)
All Formal education is oriented towards the continuity of one's education to carry out formal learning activities from the pre-school level to the university level. This article asks about the involvement of non-formal education to fulfil the learning needs of students during the Covid-19 epidemic as a form of companion, complement, support and requirement. This article uses a qualitative descriptive design that takes the ideas, sources and theories based on reference books, related journals and experiences as well as from sources those who are experienced in their fields. So this article, the author states that the involvement of non-formal education is divided into two points, namely: 1) Direct involvements: a) extracurricular involvement, b) technology system involvement of subjects matters, c) involvement of school activity companions, d) involvement of supporting of vision and mission of the school. 2) Indirect involvements: a) involvement of companion learning resources needed, b) involvement of flexibility learning activities, c) involvement of potential trainers of students, d) involvement of pre-requisites for admission to favourite study and e) involvement the lifelong education's changement.